From Social Claims To Social Evidence: Social Washing Risk In Islamic Banking - Garbo, Anom; Ahsanul Amal, Muhammad; Isnaini, Laili (Robust: Research of Business and Economics Studies, 2026)
This narrative literature review examines social washing risk in Islamic banking, defined as the gap between social claims grounded in Islamic identity and verifiable evidence of social performance. Existing studies have discussed CSR disclosure, Shariah governance, maqasid al-Shariah, ESG reporting, and greenwashing, yet the specific risk that Islamic banks may use religious and social narratives symbolically remains insufficiently theorized. This article synthesizes recent literature on corporate washing, CSR decoupling, banking disclosure, Shariah supervisory boards, and sustainability assurance to develop a claim-evidence framework for assessing social credibility in Islamic banking. The review finds that social washing risk emerges when disclosure expands faster than measurable social outcomes, when Shariah governance remains form-based rather than substantive, and when assurance mechanisms verify reporting procedures but not real stakeholder impact. The article contributes by reframing Islamic banking sustainability from a disclosure problem into an accountability problem. It argues that credible Islamic banking requires stronger social evidence, independent verification, maqasid-based impact indicators, and governance structures capable of translating Islamic ethical commitments into observable welfare outcomes.